Factors influencing farmer entrepreneurs' decision to return home for sustainable rural development: evidence from China - Feng, Yiqiang; Chen, Ziao; Wang, Shuxian; Zhang, Yuxin (Frontiers in Sustainable Food Systems, 2025)
IntroductionFarmer entrepreneurs, as hybrid actors bridging urban capital and rural identity, play a vital role in promoting sustainable rural development by addressing rural hollowing and urban-rural disparities. Understanding the factors influencing their return migration decisions is therefore crucial.MethodsThis study investigates the multidimensional determinants shaping return intentions among farmer entrepreneurs using survey data from 1,573 individuals in Jintang County, China. The data were analyzed through ordered logistic regression, with robustness checks conducted via ordered probit models (AIC = 780, BIC = 845).Results(1) Economic Agency: Income level shows marginal significance (β = 0.0035, p = 0.078), with those earning over ¥100,000 annually being 1.8 times more likely to return (OR = 1.84), supporting Hypothesis H11. (2) Family Constraints: Childcare responsibilities significantly reduce return intentions (β = −0.3167, p = 0.021, OR = 0.728), while eldercare responsibilities show no significant effect (β = 0.0796, p = 0.594, OR = 1.083), possibly due to reliance on urban eldercare services. (3) Cultural Anchors: Frequent home visits (β = 0.0314, p = 0.001, OR = 1.032) and strong hometown identity (β = 0.1578, p = 0.011, OR = 1.171) jointly enhance return intentions. Monthly returnees are 3.2 times more likely to commit to resettlement than annual visitors. (4) Selective Policy Impact: General policy awareness does not influence return decisions (β = −0.0099, p = 0.863, OR = 0.990), while targeted expectations for local economic development (β = 0.3914, p = 0.001, OR = 1.479) and education improvements (β = 0.3704, p = 0.033, OR = 1.448) significantly encourage return.DiscussionThe findings underscore the importance of cultural identity, family dynamics, and targeted policy design in shaping the return decisions of farmer entrepreneurs. We recommend three policy directions: building cultural governance platforms to reinforce local identity, developing rural childcare cooperatives to reduce family constraints, and creating tailored policy communication strategies to improve engagement and responsiveness. These interventions can support SDG-aligned rural revitalization in post-migration contexts.